2015
DOI: 10.1038/ncomms9920
|View full text |Cite
|
Sign up to set email alerts
|

Efficient near-infrared up-conversion photoluminescence in carbon nanotubes

Abstract: Photoluminescence phenomena normally obey Stokes' law of luminescence according to which the emitted photon energy is typically lower than its excitation counterparts. Here we show that carbon nanotubes break this rule under one-photon excitation conditions. We found that the carbon nanotubes exhibit efficient near-infrared photoluminescence upon photoexcitation even at an energy lying >100–200 meV below that of the emission at room temperature. This apparently anomalous phenomenon is attributed to efficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 48 publications
6
127
1
Order By: Relevance
“…In addition, Akizuki et al. reported that the SWNTs possessing both high E 11 and E 11 * PL efficiencies have the potential to be used as up‐conversion PL materials …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Akizuki et al. reported that the SWNTs possessing both high E 11 and E 11 * PL efficiencies have the potential to be used as up‐conversion PL materials …”
Section: Resultsmentioning
confidence: 99%
“…In addition, Akizuki et al reported that the SWNTs possessing both high E 11 and E 11 *P Le fficienciesh ave the potential to be used as up-conversion PL materials. [13] Meanwhile, Larciprete et al reported ad ual path mechanism for the thermal reduction of graphene oxide (GO) depending on the coverage of oxygen atoms. [8b] When the oxygen coverage on GO wasl ow,t he elimination of oxygen atomsp roceeded preferentially.I nc ontrast, the CO/CO 2 evolution reaction concluded with the elimination reaction of oxygen when the oxygen coverage was high.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, CNTs have shown near-infrared photoluminescence via a one photon-activated upconversion mechanism. 289 A photoreduction (as opposed to the more usual photo-oxidation) mechanism has been shown to be advantageous for cancerous tumors. 32 Some organic chromophores exhibiting features such as “photoblinking”, leading to a low signal-to-noise ratio using time-resolved imaging, have been reported.…”
Section: Challenges Perspectives and Critical Remarksmentioning
confidence: 99%
“…This, at first sight, astonishing observation is due to intrinsic energy transfer. PL up‐conversion, sometimes called anti‐Stokes photoluminescence (ASPL), has been observed in many semiconductor materials, such as II–VI and III–V compound nanomaterials, in bulk semiconductors, or in carbon nanotubes . The excess energy can be provided by high‐energy free carriers through an Auger process, by phonons, or by a second photon in a coherent or two‐step process .…”
Section: Introductionmentioning
confidence: 99%
“…PL up-conversion, sometimes called anti-Stokes photoluminescence (ASPL), has been observed in many semiconductor materials, such as II-VI and III-V compound nanomaterials, [1][2][3][4][5][6][7] in bulk semiconductors, [8][9][10] or in carbon nanotubes. [11] The excess energy can be provided by high-energy free carriers through an Auger process, by phonons, or by a second photon in a coherent or two-step process. [5] Two-photon absorption can be achieved through high-power excitation, typically provided by short laser pulses.…”
Section: Introductionmentioning
confidence: 99%